FAKTOR YANG BERHUBUNGAN DENGAN PENATALAKSANAAN PENANGGULANGAN SAMPAH DENGAN STRATEGI REDUSE, REUSE, RECYCLE DI KECAMATAN BATANGTORU KABUPATEN TAPANULI SELATAN - Dewi, Mustika; Batubara, Saiful (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2024)
The 3R method or Reuse, Reduce and Recycle is one of the best ways to manage and deal with various types of plastic waste. The application of this system is also very good for managing waste from various types of plastic from safe to toxic. Types of analytical quantitative research with survey techniques. Analytical surveys are intended to explain a condition. Analytical surveys usually attempt to respond to why. The population totaled 93 respondents in the Batangtoru sub-district, using a proportional random sampling technique. Data analysis was carried out univariately and bivariate with the chi-square test. The basis for decision-making is based on the level of significance (p-value), with the following criteria: ho is rejected if p <α 0.05, then there is a significant correlation or relationship between the variables ho is accepted if p > α 0.05, then there is no significant correlation or relationship between variables. The results of the study using the chi square test obtained a p value of 0.436 (p <0.05) it can be concluded that there is no relationship between knowledge and waste management with last year's 3R strategy, results using the chi square test p value obtained 0.314 (p <0.05) it can be concluded that there is no relationship between education and management of waste management with last year's 3R strategy, results using the chi square test p value value obtained 0.256 (p <0.05) it can be concluded that there is no relationship between perception and management of waste management with the 3R strategy last year, the results using the chi square test p value obtained 0.031 (p <0.05) can be obtained conclude that there is no relationship between income and management of waste management with the 3R strategy last year, the results using the chi square test p value obtained 0.000 (p <0.05) it can be concluded that there is a relationship between the role of government and community leaders with management of management waste management with the 3R strategy last year, the results using the chi square test, the p value was obtained 0.003 (p <0.05) it can be concluded that there is a relationship between facilities and markets with the management of waste management with the 3R strategy last year